Qualitative classification of the breast cancer genome and clustering of the cancer gene network - Fatema, Kaniz; Shabnam, Shejuti; Saha, Akash (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.